Bimbingan Klasikal Berbasis Dzikir untuk Meningkatkan Keterampilan Emosi Anak Panti Asuhan Rumah Harapan Samarinda - Nursa'adah, Yessi; Almatubah; Nurfadilah, Rohmah; Atussolihah, Mar; Savitri, Rahmi Dwi; Repalina; Indrayani, Dhea; Kusuma, Rudy Hadi (Fisip UIN Sunan Gunung Djati Bandung, 2025)
This study aims to enhance emotional regulation skills among orphanage children through a classical guidance approach based on dzikir (Islamic remembrance). Children living in orphanages often face limitations in emotional caregiving, which affects their affective balance. The activity was carried out in two face-to-face sessions at Rumah Harapan Orphanage in Samarinda, involving 15 children aged 8–12 years. The methods used included interactive lectures, group discussions, observations, games, and dzikir practices such as